2000
DOI: 10.1093/jnci/92.24.2023
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Receptor Gene CAG Repeats, Plasma Testosterone Levels, and Risk of Hepatitis B-Related Hepatocellular Carcinoma

Abstract: Higher levels of androgen signaling, reflected by higher testosterone levels and 20 or fewer AR-CAG repeats, may be associated with an increased risk of HBV-related HCC in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
124
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 24 publications
4
124
0
Order By: Relevance
“…However, the male/female ratio of B-HCC patients was 6.4, which is much higher than that the 1.7 male/ female ratio of C-HCC patients. Sex hormone levels have been implicated in relation to hepatocarcinogenesis, 27,28 this might partially explain why B-HCC occurs predominantly in men. Because the majority of B-HCC was male, there were relative few female B-HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the male/female ratio of B-HCC patients was 6.4, which is much higher than that the 1.7 male/ female ratio of C-HCC patients. Sex hormone levels have been implicated in relation to hepatocarcinogenesis, 27,28 this might partially explain why B-HCC occurs predominantly in men. Because the majority of B-HCC was male, there were relative few female B-HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both higher androgen levels and more active androgen receptor (AR) gene alleles correlated with an increased risk of HCC among male hepatitis B surface antigen (HBsAg) carriers. 5,6 In AR knockout mice, the development of chemically induced HCC was delayed and the mice had fewer tumors. 7 These studies indicate that the AR axis is involved in hepatocarcinogenesis, and an active AR pathway may augment HCC risk.…”
mentioning
confidence: 99%
“…Both clinical observations and laboratory investigations have suggested that HCC is a sex hormone-dependent tumor, namely its male predominance (10), an apparent relationship to steroid hormones (11,12) and the altered status of sex hormone receptors (13,14). New therapeutic approaches with hormonal agents have thus been attempted in the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%